Determining Optical Band Gap Energy of Chitosan Biopolymer Film as the Effect of Gamma Rays Irradiation - Ariyanti, Dhita; Megasari, Kartini (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Dosimeter is one of the apparatus needed by radiation workers. From a dosimeter, radiation workers can control the absorbed dose. This research aims to investigate the properties characteristics of chitosan film for dosimeter usage. Thin-film chitosan polymer blended starch and methyl orange were prepared by phase inversion methods. The spectra were investigated by UV-Visible spectrophotometric in the wavelength range of 400-500 nm, while the optical band gap energy was investigated by the Tauch plot method. The increase in gamma rays irradiation dose affected the optical bandgap energy. It was observed that the value of band gap energy within the direct transition, indirect transition, and direct forbidden transition decreased along with the increase of gamma rays irradiation 3 and 7 kGy doses. These results indicated that gamma-ray irradiation could cause structural defects due to the excitation of non-bonding electrons. These structural defects could reduce the value of band gap energy because of the width localized states.